Computing method of thermal conductivity of heat dissipation vias in printed circuit board and its optimization. Issue 1 (2nd February 2015) - Xiao, Shuo; Zhao, Yang; Cao, Yuan; Jiang, Haifeng; Zhu, Wenliang
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to deduce a set of theory computational formula, and optimize and improve the heat conductivity of vias in printed circuit boards of electrical power apparatus. Design/methodology/approach – The authors adopted numerical simulation and experimental measurement to verify the reliability of this formula. Findings – Research result showed that 0.45 mm was the optimal bore diameter of vias; the conductivity had no obvious improvement when filling material was FR4 or Rogers, but if it was filled with texture of high thermal conductivity like soldering tine, the conductivity would improve a lot; the plating thickness of vias had a greater influence on thermal conductivity. Originality/value – Through the theory computational formula, this paper studied the influence of aperture of vias, filled materials and thickness of copper plated on vias on thermal conductivity.